Ability of medical students to calculate drug doses in children after their paediatric attachment - Oshikoya KA; Senbanjo IO; Soipe A (Centro de Investigaciones y Publicaciones Farmaceuticas, 2008)
Dose calculation errors constitute a significant part of prescribing errors which might have resulted from informal teaching of the topic in medical schools. Objectives: To determine adequacy of knowledge and skills of drug dose calculations in children acquired by medical students during their clinical attachment in paediatrics.Methods: Fifty two 5th year medical students of the Lagos State University College of Medicine (LASUCOM), Ikeja were examined on drug dose calculations from a vial and ampoules of injections, syrup and suspension, and tablet formulation. The examination was with a structured questionnaire mostly in the form of multiple choice questions.Results: Thirty-six (69.2%) and 30 (57.7%) students were taught drug dose calculation in neonatal posting and during ward rounds/ bed-side teaching, respectively. Less than 50% of the students were able to calculate the correct doses of each of adrenaline, gentamicin, chloroquine and sodium bicarbonate injections required by the patient. Dose calculation was however relatively better with adrenalin when compared with the other injections. The proportion of female students that calculated the correct doses of quinine syrup and cefuroxime suspension were significantly higher than those of their male counterparts (p<0.05 and p<0.01, respectively; Chi-square test). When doses calculated in mg/dose and mL/dose was compared for adrenalin injection and each of quinine syrup and cefuroxime suspension, there were significant differences (adrenaline and quinine, p=0.005; adrenaline and cefuroxime, p=0.003: Fischer's exact test). Dose calculation errors of similar magnitude to injections, syrup and suspension were also observed with tablet formulation.Conclusions: LASUCOM medical students lacked the basic knowledge of paediatric drug dose calculations but were willing to learn if the topic was formally taught. Drug dose calculations should be given a prominent consideration in the undergraduate medical curriculum in Nigeria.